2005
DOI: 10.1254/jphs.fp0050333
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Atherosclerosis in Cholesterol-Fed Rabbits and Decrease of Expressions of Intracellular Adhesion Molecule-1 and Vascular Endothelial Growth Factor in Foam Cells by a Water-Soluble Fraction of Polygonum multiflorum

Abstract: Abstracts. Polygonum multiflorum stilbeneglycoside (PMS) is a water-soluble fraction of Polygonum multiflorum Thunb., one of the most famous tonic traditional Chinese medicines, that has protective effects on the cardiovascular system. The purpose of the present study is to elucidate the effects of PMS on macrophage-derived foam cell functions and the reduction of severity of atherosclerosis in hypercholesterolemic New Zealand White (NZW) rabbits. NZW rabbits were fed for 12 weeks with a normal diet, a high ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…Lv et al demonstrated that PMS could increase the activities of SOD and glutathione peroxidase (GSH-Px) in the serum and organs (liver, heart, and brain) of senile rats and decrease the level of 2-thiobarbituric acid-reactive substances (TBARS) in vivo [20] . Additionally, PMS was found to possess an anti-atherosclerotic and hypolipidemic activity [21] . Therefore, PMS may have protective effects against I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al demonstrated that PMS could increase the activities of SOD and glutathione peroxidase (GSH-Px) in the serum and organs (liver, heart, and brain) of senile rats and decrease the level of 2-thiobarbituric acid-reactive substances (TBARS) in vivo [20] . Additionally, PMS was found to possess an anti-atherosclerotic and hypolipidemic activity [21] . Therefore, PMS may have protective effects against I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…is one of the most important and widely used Chinese medicinal plants belonging to Polygonaceae family, and is officially listed in the Chinese Pharmacopoeia (China Pharmacopoeia Committee 2005). In traditional Chinese medicine, both the rhizomes and the old stems are used as tonic in many remedies for anemia, neurasthenia, and hypercholesterolemia (Yang et al 2005;Wang et al 2009). The clinically demonstrated major bioactive compounds of F. multiflora are various aromatic polyketides including stilbenes and anthraquinones (Lin et al 2003;Yao et al 2006); more precisely, 2,3,5,4'-tetra-hydroxy-stilbene-2-O-β-D-glucoside (TSG), emodin, rhein, physcion and chrysophanol.…”
Section: Introductionmentioning
confidence: 99%
“…ICAM-1 (Intracellular Adhesion Molecule 1) is a molecule involved in attraction and adhesion of inflammatory cells to endothelial and epithelial cells, and its soluble form, sICAM-1, is linked to activation of these cells in pathological responses [38]. It is up-regulated in liver associated diseases, such as in hepatitis C [38].…”
Section: Resultsmentioning
confidence: 99%